Metastatic carotid body tumor: a rare condition - S. Yescas-Castellanos, Salvador; Luna-Peteuil, Zelik; Y. Garcia Ortega, Dorian; Luna-Ortiz, Kuauhyama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Carotid body tumors (CBTs), or carotid glomus tumors, are rare, slow-growing benign neoplasms arising from the carotid body chemoreceptor. Metastatic disease is uncommon and poorly understood. We report the case of a 53-year-old male with a Shamblin type IIIB CBT, treated with a hybrid approach involving stent placement followed by en bloc resection. He remained disease-free for 116 months before developing regional recurrence along with pulmonary, bone, and brain metastases, which were managed with palliative radiotherapy. The patient died three years after the onset of the first metastases. This case highlights that CBT metastasis may arise more than a decade after initial treatment, underscoring the importance of long-term follow-up and multidisciplinary management.